Raising Up Precious Mankind Project: Intensive English Learning Community Service to Improve English Proficiency Skills of Children in Tanjung Malaka, Tamalate, Makassar - Wijaya, Ghovinda Fitra; Cendana, Wiputra; Sorn, Vannak (Actual Insight, 2025)
Indonesia is striving to achieve its ambitious Vision of Golden Indonesia 2045, which requires a globally competitive human resource base. To realize this goal, proficiency in international languages particularly English has become an essential skill. However, recent data show that Indonesia ranks 80th out of 116 countries in terms of English language proficiency, with the city of Makassar among those with low scores. In response to this issue, an initiative called Raising Up Precious Mankind was established on February 11, 2024. This initiative focuses on enhancing the skills of children in Tanjung Malaka neighbourhood, Tanjung Merdeka urban village, Tamalate District, Makassar City. Through various educational and training activities, the program has supported children in improving their English fluency, numeracy, and artistic abilities. Beyond its direct impact on the children, this community engagement program has evolved into a platform that encourages broader civic participation. It also serves as a space for university and high school students to develop essential skills such as critical thinking, creativity, communication, and collaboration.